EXPERIENCE OF A NEW DEVICE TECHNOLOGY CFA PILES FOR STRENGTHENING THE FOUNDATIONS - , И. К., Н. Р., В. И. (Municipal economy of cities. Series: «Economy science», 2013)
Some results of a new technology application of the drill injected stilts with small diameter and with an additional dispersed reinforcement of a polymeric fiber is described. Results are obtained by improved technology in laboratory conditions, therefore verification of the technology in building conditions.